The dual effects of leader bottom-line mentality on employee innovation behavior: the mediating role of willingness to take risks and the moderating role of work values - Shiwen Luo; Qi Fan; David Yoon Kin Tong (Frontiers in Psychology)
IntroductionIn the VUCA era, employee innovation behavior is critical to a enterprise success. In China’s high power distance and collectivist culture, employee innovation behavior is often influenced by leadership authority, resulting in distinct patterns of proactive and reactive innovation behavior that differentially predict innovation performance. Innovation is influenced not only by leadership type but also by leadership mindset. As a unidimensional approach, leader bottom-line mentality focuses on bottom-line profits while neglecting other important factors. However, its distinct predictive relationships with proactive versus reactive innovation behaviors remain insufficiently examined.MethodsThis study employed a two-stage survey method in which a questionnaire survey was conducted with employees from 13 innovation-driven enterprises, and 351 valid responses were ultimately collected. Using SPSS and MPLUS software, the data were analysed through reliability and validity tests, confirmatory factor analysis, descriptive statistics, and linear regression to validate the proposed research hypotheses.ResultsLeader bottom-line mentality is significantly negatively associated with proactive innovation behavior but positively associated with reactive innovation behavior. Moreover, willingness to take risks mediates the relationship between leader bottom-line mentality and employee innovation behavior. Additionally, intrinsic work values moderate the relationship between managers’ bottom-line mentality and risk-taking, which promotes proactive innovation behavior and reduces reactive innovation behavior. On the other hand, extrinsic work values positively moderate the relationship, enhancing reactive innovation behavior and reducing proactive innovation behavior.DiscussionAs a unidimensional mentality, leader bottom-line mentality exhibits a dual predictive pattern with respect to employee innovation behavior: it positively predicts reactive innovation behavior while negatively predicting proactive innovation behavior. Notably, these predictive relationships are contingent upon work values: intrinsic work values attenuate the observed dual pattern, whereas extrinsic work values amplify these associations.